2013
DOI: 10.1371/journal.pone.0063902
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose BPA Exposure Alters the Mesenchymal and Epithelial Transcriptomes of the Mouse Fetal Mammary Gland

Abstract: Exposure of rodent fetuses to low doses of the endocrine disruptor bisphenol A (BPA) causes subtle morphological changes in the prenatal mammary gland and results in pre-cancerous and cancerous lesions during adulthood. To examine whether the BPA-induced morphological alterations of the fetal mouse mammary glands are a) associated with changes in mRNA expression reflecting estrogenic actions and/or b) dependent on the estrogen receptor α (ERα), we compared the transcriptomal effects of BPA and the steroidal es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 46 publications
(66 reference statements)
6
80
0
Order By: Relevance
“…These include the above mentioned Ho et al (2006) and Tang et al (2012) studies that report gene expression modulation in the prostate of Sprague-Dawley rats treated subcutaneously with 10 μg BPA/kg bw/day on PND 1, 3, and 5. The modulation of female mammary gland gene expression in rodent models was reported by Moral et al (2008; Sprague-Dawley rats, 25 and 250 μg BPA/kg bw/day, daily gavage, from GD 10 to 21), Wadia et al (2013; ERα (+/+) and ERα (−/−) C57BL/6 mice, 250 ng BPA/kg BW/day, subcutaneous osmotic pump, from GD 8 to 19), and Dhimolea et al (2014; Wistar-Furth rats, 250 μg BPA/kg bw/day, subcutaneous osmotic pump, from GD 9 to PND 1). Similarly, in our study, several genes were found to be modulated both in PND 4 prostate and female mammary glands in the “low BPA” dose range versus the vehicle control.…”
Section: Discussionmentioning
confidence: 94%
“…These include the above mentioned Ho et al (2006) and Tang et al (2012) studies that report gene expression modulation in the prostate of Sprague-Dawley rats treated subcutaneously with 10 μg BPA/kg bw/day on PND 1, 3, and 5. The modulation of female mammary gland gene expression in rodent models was reported by Moral et al (2008; Sprague-Dawley rats, 25 and 250 μg BPA/kg bw/day, daily gavage, from GD 10 to 21), Wadia et al (2013; ERα (+/+) and ERα (−/−) C57BL/6 mice, 250 ng BPA/kg BW/day, subcutaneous osmotic pump, from GD 8 to 19), and Dhimolea et al (2014; Wistar-Furth rats, 250 μg BPA/kg bw/day, subcutaneous osmotic pump, from GD 9 to PND 1). Similarly, in our study, several genes were found to be modulated both in PND 4 prostate and female mammary glands in the “low BPA” dose range versus the vehicle control.…”
Section: Discussionmentioning
confidence: 94%
“…Our in vitro data also showed similar biological effects, which further supported our in vivo data. Previous data have indicated that BPA affects the expressions of genes related to apoptosis signaling pathways, rather than the ERα and ERβ signaling pathways in epithelium cells (Wadia et al 2013). The density of mammary buds significantly increases when rhesus monkeys are exposed to BPA, and acceleration of mammogenesis is observed, but the changes in ER expression are not significant (Tharp et al 2012).…”
Section: Discussionmentioning
confidence: 94%
“…The results are presented as mean ± SD. Asterisk (* or **) indicates significant difference (P < 0.05 or P < 0.01) discussed (Kim et al 2004;Venkata et al 2006;Wadia et al 2007Wadia et al , 2013Dairkee et al 2013;Paulose et al 2015;Bhan et al 2014;Dhimolea et al 2014). According to the epidemiological investigations carried out in Europe and America in the past 50 years, exposure to EEs during pregnancy causes enhanced morbidity of breast carcinoma in the next generations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 The positive correlation between exposure to different BPA concentrations and changes in these structures was confirmed in animal studies. 60 Oral exposure to higher doses of BPA (5 μg -5 mg/l of drinking water corresponding to 0.6 μg to 1.2 mg/kg body weight) resulted in alterations in the number of terminal endbuds. Likewise, after exposure to DES, perinatal exposure to BPA increases epithelial cell numbers in the mammary gland in adulthood.…”
mentioning
confidence: 99%